Strategi Manajemen Pembelajaran Matematika dengan Pendekatan Deep Learning pada Siswa Kelas 1 SD - Nomas Indah Larasati; Dian Hidayati; Muhammad Zuhaery (Universitas Negeri Malang, 2026)
Abstract: Mathematics learning in early elementary school requires strategies that build students' in-depth conceptual understanding through process stages, not just outcomes, in accordance with their cognitive developmental stages. This study aims to describe mathematics learning management strategies using a deep learning approach for first-grade students at Muhammadiyah Elementary School, Komplek Kolombo.The study used a qualitative, descriptive approach. Data were obtained through interviews, observations, and documentation involving the principal, vice principal for curriculum, and first-grade teachers. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing, with the assistance of the ATLAS.ti 9 application. The results of the study indicate that the deep learning-based mathematics learning management strategy is implemented through integrated planning, organizing, implementing, and monitoring stages. In the planning stage, teachers analyze student characteristics, the curriculum, and learning needs to design meaningful learning. The organizing stage includes classroom management, scheduling, and the fair and flexible use of resources and teaching aids. The learning implementation applies differentiation practices, mentoring supervision, and reflective learning communication. The monitoring stage is carried out through in-depth cognitive assessment, problem-solving evaluation, and standardization and reporting that emphasize thinking processes and conceptual understanding. It is concluded that the implementation of the deep learning-based mathematics learning management strategy can encourage student-centered learning, strengthen conceptual understanding, and develop critical thinking and problem-solving skills from the early grades of elementary school. Keywords: learning management, mathematics, deep learning, elementary school, qualitative research. Abstrak: Pembelajaran matematika di kelas awal sekolah dasar menuntut strategi yang mampu membangun pemahaman konsep siswa secara mendalam melalui tahapan proses tidak hanya hasil, sesuai dengan tahap perkembangan kognitifnya. Penelitian ini bertujuan untuk mendeskripsikan strategi manajemen pembelajaran matematika dengan pendekatan deep learning pada siswa kelas 1 di SD Muhammadiyah Komplek Kolombo. Penelitian menggunakan pendekatan kualitatif dengan jenis deskriptif. Data diperoleh melalui wawancara, observasi, dan dokumentasi yang melibatkan kepala sekolah, wakil kepala sekolah bidang kurikulum, dan guru kelas 1. Analisis data dilakukan menggunakan model interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, serta penarikan kesimpulan, dengan bantuan aplikasi ATLAS.ti 9. Hasil penelitian menunjukkan bahwa strategi manajemen pembelajaran matematika berbasis deep learning dilaksanakan melalui tahapan perencanaan, pengorganisasian, pelaksanaan, dan pengawasan yang saling terintegrasi. Pada tahap perencanaan, guru melakukan analisis karakteristik siswa, kurikulum, serta kebutuhan belajar untuk merancang pembelajaran bermakna. Tahap pengorganisasian mencakup pengelolaan kelas, penjadwalan, serta pemanfaatan sumber daya dan alat peraga secara adil dan fleksibel. Pelaksanaan pembelajaran menerapkan praktik diferensiasi, supervisi pendampingan, serta komunikasi belajar yang reflektif. Tahap pengawasan dilakukan melalui penilaian kognitif mendalam, evaluasi problem solving, serta standardisasi dan pelaporan yang menekankan proses berpikir dan pemahaman konsep. Disimpulkan bahwa penerapan strategi manajemen pembelajaran matematika berbasis deep learning mampu mendorong pembelajaran yang berpusat pada siswa, memperkuat pemahaman konseptual, serta mengembangkan kemampuan berpikir kritis dan pemecahan masalah sejak kelas awal sekolah dasar. Kata kunci: manajemen pembelajaran, matematika, deep learning, sekolah dasar, penelitian kualitatif.